Laparoscopic vs. open colectomy for T4 colon cancer: A meta-analysis and trial sequential analysis of prospective observational studies - Chen, Peng; Zhou, Hang; Chen, Chuwen; Qian, Xin; Yang, Lie; Zhou, Zongguang (Frontiers in Surgery, 2022)
Background To evaluate short- and long-term outcomes of laparoscopic colectomy (LC) vs. open colectomy (OC) in patients with T4 colon cancer. Methods Three authors independently searched PubMed, Web of Science, Embase, Cochrane Library, and Clinicaltrials.gov for articles before June 3, 2022 to compare the clinical outcomes of T4 colon cancer patients undergoing LC or OC. Results This meta-analysis included 7 articles with 1,635 cases. Compared with OC, LC had lesser blood loss, lesser perioperative transfusion, lesser complications, lesser wound infection, and shorter length of hospital stay. Moreover, there was no significant difference between the two groups in terms of 5-year overall survival (5y OS), and 5-year disease-free survival (5y DFS), R0 resection rate, positive resection margin, lymph nodes harvested ≥12, and recurrence. Trial Sequential Analysis (TSA) results suggested that the potential advantages of LC on perioperative transfusion and the comparable oncological outcomes in terms of 5y OS, 5y DFS, lymph nodes harvested ≥12, and R0 resection rate was reliable and no need of further study. Conclusions Laparoscopic surgery is safe and feasible in T4 colon cancer in terms of short- and long-term outcomes. TSA results suggested that future studies were not required to evaluate the 5y OS, 5y DFS, R0 resection rate, positive resection margin status, lymph nodes harvested ≥12 and perioperative transfusion differences between LC and OC. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022297792.